Educar-se em pontos salientes: produção e circulação do livro em braille no Imperial Instituto dos Meninos Cegos - Gabriel Bertozzi de Oliveira e Sousa Leão (2023)
The thesis aims to analyze the processes related to the conception, production and circulation of the braille textbook in Brazil during the second half of the nineteenth century, particularly at the Imperial Instituto dos Meninos Cegos. The historical documents consulted and kept by various historical collections are composed of: letters, notes, lists and reports received or prepared by the directors and people related to the Institute; legislation and official documents of the Brazilian Empire; material from newspapers, almanacs and publications of that time; students' braille productions; as well as textbooks and school manuals in ink and braille used in the institution. The Imperial Instituto dos Meninos Cegos, institution founded in 1854, in Rio de Janeiro, capital of the Brazilian Empire, was the first formalized educational space of Brazil aimed specifically to teach people with disabilities and it was a pioneer in the ways of printing textbooks in the Braille System. The institution had two workshops, a typographic and a binding, that were in constant production, despite the limited production of relief books, which operated until the end of the Brazilian Empire, and were expanded in the transition to the Republic. Working with an intense circulation of books and other pedagogical materials, based on the relationship with the French Institute for the Blind, its library was being structured with books prepared by its workshops, handwritten by students and also others imported from Europe; in French or Portuguese; originals in braille or adaptations of books in ink. This scenario enabled, for the first time, educational actions for the blind with accessible pedagogic material. The expansion of the Institute’s library allowed a gradual increase and diversification of the institutional curriculum, expanding circulation and reading practices with books printed in salient points. The practices of preparing the book, organized and accomplished by the blind students, revealed a unique situation of more intense contact between these students and the books used by them, different from what happened in schools for sighted people. In the transformation of a book in ink into a book in braille, many elements of the works were re-signified due to adaptations for reading with touch and better understanding for blind readers. This translational-interpretative process was reflected in the elaboration of new meanings of the text. The quantity, diversity, discourses and materiality of books in braille allowed the creation of reading experiences different from those carried out with books in ink, influenced mainly by their way of decoding: touch. By this process, new meanings related to the book could be appropriated by the reader. All these dynamics involved with the braille book provided support to influence the construction of students' identities and distance themselves from the link between blindness and stigma. Those practices allowed the development of a sense of belonging to a group that shared not only a physical characteristic, but also significant experiences related to this cultural artifact.